The digital archives handbook : a guide to creation, management, and preservation - Purcell, Aaron D., 1972- (Lanham, Maryland : Rowman & Littlefield, 2019)
'This edited volume explores the challenges of digital donations with essays from archivists who have developed methods to provide access to a diverse range of digital materials found in government, private, and academic archives'--
Acquisitions, appraisal, and arrangement / Lisa Calahan -- Description and delivery / Dorothy Waugh -- Digital preservation / Bertram Lyons -- Digital forensics and curation / Martin Gengenbach -- Contracts, intellectual property, and privacy / Heather Briston -- Performing arts collections / Vincent J. Novara -- Oral history collections / Douglas A. Boyd -- Architectural and design collections / Aliza Leventhal -- Congressional collections / Danielle Emerling -- Email / Matthew Farrell.
Includes bibliographical references and index.
Keywords: Electronic records -- Management -- Handbooks, manuals, etc; Digital preservation -- Handbooks, manuals, etc; Archives -- Collection management -- Handbooks, manuals, etc; Archives -- Access control -- Handbooks, manuals, etc